2017
DOI: 10.3382/ps/pex185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary threonine supplementation on intestinal barrier function and gut microbiota of laying hens

Abstract: The effects of supplemental dietary threonine (Thr) on laying performance, expression of intestinal mucin 2 (MUC2) and secretory IgA (sIgA), and intestinal microbiota of laying hens fed a low CP diet were investigated. A total of 240 Lohmann Brown laying hens, 28 wk of age, was allocated to 3 dietary treatments, each of which included 5 replicates of 16 hens. Hens were fed a control diet (16% CP), a low CP diet (14% CP), or a low CP diet supplemented with 0.3% L-Thr for 12 weeks. Chemical analyses of the diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 33 publications
9
54
0
2
Order By: Relevance
“…During the processes of nutrition, metabolism, physiology and immunity, the intestinal microbiota can promote digestion and absorption of nutrients, stimulate the immune response of the host and enhance resistance to infection ). In addition to animal age, hygiene and environmental factors, diet is a major factor that can influence the microbial population in the intestinal tract (Dong et al 2017). Previous studies suggested that dietary supplementation of forage had an impact on poultry performance by modifying the gut microbial structure to a bacterial community that is more conducive to host growth (Jiang et al 2014;Saeed et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the processes of nutrition, metabolism, physiology and immunity, the intestinal microbiota can promote digestion and absorption of nutrients, stimulate the immune response of the host and enhance resistance to infection ). In addition to animal age, hygiene and environmental factors, diet is a major factor that can influence the microbial population in the intestinal tract (Dong et al 2017). Previous studies suggested that dietary supplementation of forage had an impact on poultry performance by modifying the gut microbial structure to a bacterial community that is more conducive to host growth (Jiang et al 2014;Saeed et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…increased the diversity of intestinal microbiota in squabs. It is widely believed that the higher the diversity, the better the intestine health, because the diversity is one of the key determinants of colonization resistance against invading pathogens [51]. The result indicated that squabs had greater resistance in LA1% and LA2%.…”
Section: Discussionmentioning
confidence: 96%
“…На даному етапі деталізація технології вирощування здійснюється на високому рівні з врахуванням факторів, яким раніше вчені і практики не приділяли уваги. Наприклад, мікроструктурні зміни в кишечнику, зокрема, в слизових оболонках від яких залежить асиміляція нутрієнтів, стан і процеси які відбуваються у кишечнику визначають здоров'я птиці та ефективність використання поживних і біолого активних речовинах, що в свою чергу, пов'язано з інтенсивністю росту і розвитку, конверсією корму та іншими важливими господарськими показниками в птахівництві (Grozina, 2014;Filho et al, 2015;Dong et al, 2017). Відомо, що у птахівництві біля 70% собівартості продукції припадає на вартість кормів.…”
Section: вступunclassified